Utilization of Brown Seaweed as a Functional Dietary Salt and Source of Antioxidant Activity: A Review - Astriani, Aisyah; Nurjanah, Nurjanah (Fakultas Pertanian Universitas Samudra, 2023)
Seaweed contains minerals and active compounds that have potential antioxidant, antihypertensive and other health benefits. As a result of this potential, seaweed is now widely used in the fields of medicine, cosmetics, fertilizer, bioenergy and food. In the food industry, seaweed can be used as raw material for making salt with low sodium and high potassium content so that it is beneficial for human health. This literature review presents several discussions and relevant literature sources regarding the manufacturing process and components contained in seaweed salt, such as heavy metal content, mineral composition, Na:K, NaCl ratio, and antioxidant activity. This literature study uses an exploratory descriptive approach by collecting information from a lot of previous research literature, in the form of national and international journals as well as online databases such as Researchgate, Directory of Open Access Journals and Google Scholar.